2017
DOI: 10.1016/j.scriptamat.2017.06.033
|View full text |Cite
|
Sign up to set email alerts
|

In situ TEM observation of FCC Ti formation at elevated temperatures

Abstract: Pure Ti traditionally exhibits the hexagonal closed packed (HCP) crystallographic structure under ambient conditions and the body centered cubic (BCC) structure at elevated temperatures. In addition to these typical structures for Ti alloys, the presence of a face centered cubic (FCC) phase associated with thin films, interfaces, or high levels of plastic deformation has occasionally been reported. Here we show that small FCC precipitates form in freestanding thin foils during in situ transmission electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…Interestingly, this γ → ε transformation mechanism does not necessarily explain the occurrence of γ nanolaminates inside the HCP ε blocks after deformation. This may rather be due to a reverse transformation (ε → γ) inside the HCP ε block. In order to discuss this hypothesis, three factors, viz., the stacking fault energy, local temperature, and local stress−strain fields, have to be considered.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this γ → ε transformation mechanism does not necessarily explain the occurrence of γ nanolaminates inside the HCP ε blocks after deformation. This may rather be due to a reverse transformation (ε → γ) inside the HCP ε block. In order to discuss this hypothesis, three factors, viz., the stacking fault energy, local temperature, and local stress−strain fields, have to be considered.…”
mentioning
confidence: 99%
“…Theoretically, a reverse transformation from the HCP ε to the FCC γ can be achieved through the motion of Shockley partials on every second {0001} basal plane with Burgers vectors a3<11¯00> . They have three equivalent glide directions, which can generate stacking faults (i.e., nanoscale FCC structure) in the HCP matrix with negligible volume expansion . Upon strain loading, the sliding of Shockley partials in the HCP ε block of the dual‐phase HEA is achieved by two possible ways ( Figure ).…”
mentioning
confidence: 99%
“…The mechanical properties of α + β alloys depend greatly on the content of the β-stabilizer element and on the type of heat treatment. Moreover, a metastable phase with a face-centred cubic (fcc) structure (called γ phase) has been reported in pure Ti and Ti-based alloys [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental observations showed that the presence of the FCC phase was associated with thin films, interfaces, powders, high levels of plastic deformation, and heat-treated Ti alloys. Recent work shows that the small FCC precipitates formed in freestanding thin foils during in situ transmission electron microscope (TEM) heating 8 . Experimental results indicate that the stability of FCC Ti in thin films is related to the film thickness, surface orientation, and temperature [9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%